Origin of carbonatites in the South Qinling orogen: Implications for crustal recycling and timing of collision between the South and North China Blocks - Xu, C.; Chakhmouradian, A.; Taylor, R.; Kynicky, J.; Li, W.; Song, W.; Fletcher, Ian (Pergamon, 2014)
Most studies of compositional heterogeneities in the mantle, related to recycling of crustal sediments or delaminated subcontinental lithosphere, come from oceanic setting basalts. In this work, we present direct geochronological and geochemical evidence for the incorporation of recycled crustal materials in collision-related carbonatites of the South Qinling orogenic belt (SQ), which merges with the Lesser Qinling orogen (LQ) to separate the South and North China Blocks. The SQ carbonatites occur mainly as stock associated with syenites. The data presented here show that zircon from the syenites yields an age of 766 ± 25 Ma, which differs significantly from the age of primary monazite from the carbonatites (233.6 ± 1.7 Ma). The syenites contain lower initial 87Sr/86Sr and higher εNd values. This indicates that the carbonatites do not have genetically related with the silicate rocks, and were directly derived from a primary carbonate magma generated in the mantle. The carbonatites show a Sr–Nd isotopic signature similar to that of the chondritic uniform reservoir (CHUR), and parallel Sm–Nd model ages (TCHUR) of 190–300 Ma. However, the rocks have extremely variable Pb isotopic values straddling between the HIMU and EM1 mantle end-members. Most carbon and oxygen isotopic compositions of the SQ carbonatites plot outside the field for primary igneous carbonates. Their δ13C shows higher value than a ‘normal’ mantle, which implies an incorporation of recycled inorganic carbon. The carbonatites were emplaced close to the Mianlue suture, and followed the closure of the Mianlue ocean and Triassic collision of the South and North China Blocks.However, direct melting of the subducted Mianlue oceanic crust characterized by high εNd and low (EM1-like) 206Pb/204Pb values cannot explain the CHUR-like Nd signature and the Pb isotopic trend toward HIMU in the SQ carbonatites. We conclude that their parental magma was derived from a source incorporating the Mianlue oceanic crust mixed with an asthenospheric (or deeper) material characterized by high Pb and low Nd isotopic values. This material represents a deep-seated Proterozoic carbonate component recycled via mantle convection or localized upwelling. Notably, this model cannot explain the isotopic compositions of the Late Triassic (209–221 Ma) carbonatites in the LQ, characterized by a mantle-derived δ13C, but EM1-like Sr–Nd–Pb isotopic compositions. This signature is best explained in terms of delamination of the lower continental crust thickened during the collision of the South and North China Blocks, and partial incorporation of the delaminated material into the LQ mantle source. Modeling of the measured Sr–Nd–Pb isotopic variations suggests that the source of the LQ carbonatites could be produced by mixing of 80–85% of mantle material and 15–20% of delaminated lower continental crust. The emplacement of the SQ and LQ carbonatites marked a gradual transition from a compressional tectonic regime, brought about by the collision of the South and North China Blocks to intra-orogenic extension in the waning stages of the Triassic orogeny.